Corrosion-resistant plastic bucket composite material and preparation method thereof
By adding a modified toughening agent and reinforcement to the polypropylene plastic bucket, a composite material is formed, which solves the problems of insufficient toughness, weather resistance and corrosion resistance of the polypropylene plastic bucket, and achieves higher material performance.
Patent Information
- Application Number
- CN202411972832.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-30
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2044-12-30
AI Technical Summary
Polypropylene plastic barrels are susceptible to external shock damage during shipment of large storage containers, and are insufficient weather resistance and corrosion resistance, which limits their application range.
Using a composite material, including polypropylene resin, polyethylene resin, modified toughening agent, reinforcement, antioxidant, lubricant and maleic anhydride grafted polypropylene, the toughness, weather resistance and corrosion resistance of the material are improved by adding the modified toughening agent and reinforcement.
It significantly improves the toughness, weather resistance and corrosion resistance of plastic barrel composite materials, can better resist external shocks, ultraviolet rays, oxygen and high temperatures, and extend its service life.
Smart Images

Figure BDA0005219817710000111
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of plastic barrel composite materials, and in particular to a corrosion-resistant plastic barrel composite material and a preparation method thereof. Background Art
[0002] Commonly used materials for plastic barrels are polypropylene, polyethylene, polyvinyl chloride, etc. Polypropylene, as a semi-crystalline thermoplastic, has high impact resistance, strong mechanical properties, and can resist corrosion from a variety of organic solvents and acids and alkalis. Using it as a plastic barrel material can be widely used in liquids and solid items in chemical raw materials, pesticides, lubricants, coatings, medicines, food, hardware and electronics, electromechanical and other industries.
[0003] However, the toughness of polypropylene is average. It is inevitable that external impact failure will occur during the transportation of large storage containers, which can easily cause leakage of the storage medium and pose a major safety hazard. At the same time, the weather resistance of polypropylene materials is poor, which will cause the barrel material to be easily affected by ultraviolet rays, oxygen and high temperature during outdoor use, resulting in material aging, discoloration, performance degradation and cracking, which greatly limits the application of polypropylene barrel materials. In addition, plastic barrels are often difficult to meet the requirements when facing high-intensity use environments and extreme chemical corrosion. Therefore, in response to the increased requirements for the use of polypropylene plastic barrels, it is necessary to prepare a plastic barrel composite material with good toughness, good weather resistance and good corrosion resistance to meet actual application needs. Summary of the invention
[0004] In order to solve the above technical problems, the present invention provides a corrosion-resistant plastic barrel composite material and a preparation method thereof.
[0005] The purpose of the present invention can be achieved through the following technical solutions:
[0006] A corrosion-resistant plastic barrel composite material comprises the following raw materials in parts by weight: 70-80 parts of polypropylene resin, 20-30 parts of polyethylene resin, 8-15 parts of modified toughening agent, 10-20 parts of reinforcing agent, 0.3-0.6 parts of antioxidant, 2-4 parts of lubricant, and 1-3 parts of maleic anhydride grafted polypropylene;
[0007] The antioxidant is one of antioxidant 1010 or antioxidant 168, and the lubricant is calcium stearate;
[0008] The modified toughening agent is prepared by the following steps:
[0009] Step A1, tetraethyl orthosilicate and dimethyldiethoxysilane are mixed and stirred in deionized water for 10 minutes to form a mixed solution, and then the mixed solution is slowly added dropwise to ethanol, stirred and reacted for 2-3 hours, and then γ-glycidyloxypropyltrimethoxysilane is slowly added, stirred and reacted for 0.5-1.5 hours, and then 10wt% ammonia water is added, and the mixture is transferred to a 60°C water bath and allowed to stand for 30 minutes, centrifuged, washed, and dried to obtain functionalized silicone microspheres;
[0010] Step A2, adding 2,2-dihydroxymethylpropionic acid, tetrabutylammonium bromide and N,N-dimethylformamide to the functionalized organosilicon microspheres, mixing, first purging with nitrogen for 10 minutes, then reacting under nitrogen at 80-90° C. for 4-6 hours, rotary evaporation, adding ethyl acetate and stirring for 15 minutes, washing and drying to obtain a hyperbranched organosilicon precursor;
[0011] Step A3, after mixing the hyperbranched organosilicon precursor and potassium hydroxide, nitrogen is purged for 10 minutes, and then the temperature is raised to 90-110° C. under nitrogen conditions, and the reaction is carried out for 2-4 hours. The temperature is lowered to room temperature, propylene oxide is added, and the temperature is raised to 60-80° C. and the reaction is carried out for 3-6 hours. The temperature is lowered to 20-30° C., epichlorohydrin is added, and the temperature is raised to 60-80° C. and the reaction is carried out for 2-3 hours with stirring. A 25wt% potassium hydroxide solution is then added and stirred for 2-3 hours, and then washed. Pentaerythritol phosphate is then added at 60-80° C. and the reaction is carried out with stirring for 2.5-3.5 hours. The modified toughening agent is obtained after washing and drying.
[0012] Further, in step A1, the usage ratio of tetraethyl orthosilicate, dimethyldiethoxysilane, deionized water, ethanol, γ-glycidyloxypropyltrimethoxysilane and ammonia water is 0.05-0.1 mol: 0.03-0.06 mol: 20 mL: 80 mL: 0.01-0.03 mol: 1-3 mL;
[0013] Further, in step A2, the usage ratio of 2,2-dihydroxymethylpropionic acid, tetrabutylammonium bromide, N,N-dimethylformamide and ethyl acetate is 0.01-0.03 mol: 1.6-4.8 g: 100 mL: 30 mL;
[0014] Furthermore, in step A3, the usage ratio of the hyperbranched organosilicon precursor, potassium hydroxide, propylene oxide, epichlorohydrin, potassium hydroxide solution and pentaerythritol phosphate is 8-16 g: 0.5-1.2 g: 10-20 g: 3-8 g: 100 mL: 5-10 g.
[0015] The enhancer is prepared by the following steps:
[0016] Step B1, ultrasonically disperse zinc nitrate hexahydrate and 2,3,5,6-tetrafluoroterephthalic acid in N,N-dimethylformamide for 30 minutes, add distilled water and stir for 10 minutes, transfer to an autoclave, react at 120° C. for 24 hours, filter, wash, soak in methanol for 72 hours, filter, and dry to obtain Zn-MOF (zinc-based metal organic framework);
[0017] Step B2, sonicating Zn-MOF in deionized water for 30 minutes, then adding magnesium nitrate hexahydrate, aluminum nitrate nonahydrate and urea and sonicating for 30 minutes, then heating to 85-95°C and stirring to react for 1.5-2.5 hours, then transferring to an autoclave, reacting at 120°C for 12 hours, filtering, washing and drying to obtain Zn-MOF / magnesium aluminum hydrotalcite;
[0018] Step B3, stirring γ-methacryloxypropyltrimethoxysilane in a mixture of ethanol and deionized water for 30 minutes, then adding Zn-MOF / magnesium aluminum hydrotalcite, heating to 35-55° C. and stirring for reaction for 3-5 hours, filtering, washing, and drying to obtain an enhancer;
[0019] Further, in step B1, the usage ratio of zinc nitrate hexahydrate, 2,3,5,6-tetrafluoroterephthalic acid, N,N-dimethylformamide and distilled water is 1.5-4.5 g: 0.4-1.2 g: 30 mL: 1-2 mL;
[0020] Further, in step B2, the dosage ratio of Zn-MOF, deionized water, magnesium nitrate hexahydrate, aluminum nitrate nonahydrate and urea is 1-2 g: 100 mL: 0.8-1.2 g: 0.6-0.9 g: 1.2-1.9 g;
[0021] Furthermore, in step B3, the usage ratio of γ-methacryloxypropyltrimethoxysilane, ethanol, deionized water and Zn-MOF / magnesium aluminum hydrotalcite is 0.2-0.8 mL: 80 mL: 20 mL: 2-4 g.
[0022] A method for preparing a corrosion-resistant plastic barrel composite material comprises the following steps:
[0023] Weigh the raw materials by weight, add polypropylene resin, polyethylene resin, maleic anhydride grafted polypropylene and modified toughening agent into a stirrer, stir at 130-150°C for 2-4 hours, then add a reinforcing agent, an antioxidant and a lubricant, mix and stir evenly to obtain a mixture, then put the mixture into a twin-screw extruder for extrusion and granulation to obtain a corrosion-resistant plastic barrel composite material.
[0024] Beneficial effects of the present invention:
[0025] The plastic barrel composite material of the present invention uses polypropylene resin and polyethylene resin as main matrix resins, and adds functional additives such as modified toughening agent, reinforcing agent, antioxidant, lubricant and maleic anhydride grafted polypropylene, so as to comprehensively improve the corrosion resistance, weather resistance and toughness of the composite material; wherein, the addition of modified toughening agent improves the toughness and weather resistance of the matrix; the addition of reinforcing agent can synergistically act with antioxidant to improve the weather resistance and corrosion resistance of the matrix.
[0026] In the modified toughening agent, tetraethyl orthosilicate, dimethyldiethoxysilane and γ-glycidyloxypropyltrimethoxysilane are first used as raw materials to synthesize functionalized silicone microspheres with surface modified epoxy groups; then the functionalized silicone microspheres are reacted with 2,2-dihydroxymethylpropionic acid to obtain a hyperbranched silicone precursor containing a polyhydroxy structure; finally, propylene oxide and epichlorohydrin are used as raw materials to synthesize a hyperbranched polyether chain segment on the hyperbranched silicone precursor, and then the chain is capped with pentaerythritol phosphate to obtain a modified toughening agent. The modified toughening agent is prepared with functionalized silicone microspheres as the core layer and polyether chain segments as the shell layer. Adding it to the matrix as a toughening agent can significantly improve the toughness and weather resistance of the matrix. Among them, when the matrix is impacted by external force, the silicone microspheres in the core layer can use their three-dimensional cross-linked network molecular structure to evenly disperse the impact stress, reduce the stress concentration acting on the matrix, and thus improve the toughness of the matrix. At the same time, the polyether branched structure of the shell layer can be entangled with the polypropylene molecular chain to form a network structure, which plays a connecting and buffering role, further improving the toughness of the matrix. In addition, the phosphate structure at the end of the modified toughening agent also improves the weather resistance of the matrix. This is because the phosphorus-oxygen bond in the phosphate molecule has a higher bond energy, which can make it relatively stable under the action of ultraviolet rays and oxygen and not easy to degrade, thereby improving the weather resistance of the composite material.
[0027] In the enhancer, Zn-MOF is first prepared using zinc nitrate hexahydrate and 2,3,5,6-tetrafluoroterephthalic acid as raw materials; magnesium nitrate hexahydrate, aluminum nitrate nonahydrate and urea are then used as raw materials to synthesize magnesium aluminum hydrotalcite, and Zn-MOF is loaded on the magnesium aluminum hydrotalcite to prepare Zn-MOF / magnesium aluminum hydrotalcite; finally, the Zn-MOF / magnesium aluminum hydrotalcite is surface treated with a coupling agent to obtain the enhancer. The introduction of the reinforcing agent improves the corrosion resistance of the matrix. This is due to the synergistic effect of the magnesium-aluminum hydrotalcite and Zn-MOF in the reinforcing agent. With its unique physical structure, it has a physical barrier effect on corrosive substances such as air, water and corrosive ions. At the same time, the loaded Zn-MOF can reinforce the magnesium-aluminum hydrotalcite, further improving the corrosion resistance of the matrix; finally, the Zn-MOF / magnesium-aluminum hydrotalcite treated with a coupling agent has good dispersibility in the matrix, which can further improve the corrosion resistance of the matrix; Zn-MOF is synthesized using organic ligands containing fluorine elements. Fluorine elements have good corrosion resistance and can resist the erosion of corrosive media such as strong acids and strong alkalis, further improving the corrosion resistance of the matrix. In addition, the physical structure of the reinforcing agent also has the function of shielding ultraviolet rays, which helps to reduce the direct damage of ultraviolet rays to the matrix and improve the weather resistance of the composite material. DETAILED DESCRIPTION
[0028] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0029] Example 1: The modified toughening agent is prepared by the following steps:
[0030] Step A1, 0.05 mol of tetraethyl orthosilicate and 0.03 mol of dimethyldiethoxysilane were mixed and stirred in 20 mL of deionized water for 10 min to form a mixed solution, and then the mixed solution was slowly added dropwise to 80 mL of ethanol, stirred and reacted for 2 h, and then 0.01 mol of γ-glycidyloxypropyltrimethoxysilane was slowly added, stirred and reacted for 0.5 h, and then 1 mL of 10 wt% ammonia water was added, and the mixture was transferred to a 60° C. water bath and allowed to stand for 30 min, centrifuged, washed, and dried to obtain functionalized silicone microspheres;
[0031] Step A2, adding 0.01 mol 2,2-dihydroxymethylpropionic acid, 1.6 g tetrabutylammonium bromide and 100 mL N,N-dimethylformamide to the functionalized organosilicon microspheres, mixing, first purging with nitrogen for 10 min, then reacting under nitrogen and 80° C. for 4 h, rotary evaporation, adding 30 mL ethyl acetate and stirring for 15 min, washing and drying to obtain a hyperbranched organosilicon precursor;
[0032] Step A3, after mixing 8g of hyperbranched organosilicon precursor and 0.5g of potassium hydroxide, nitrogen was purged for 10min, and then the temperature was raised to 90°C under nitrogen conditions, reacted for 2h, cooled to room temperature, 10g of propylene oxide was added, and the temperature was raised to 60°C for reaction for 3h, and then cooled to 20°C, 3g of epichlorohydrin was added, stirred and heated to 60°C for reaction for 2h, and then 100mL of 25wt% potassium hydroxide solution was added and stirred for 2h, washed, and then 5g of pentaerythritol phosphate was added at 60°C, stirred and reacted for 2.5h, washed and dried to obtain a modified toughening agent.
[0033] The enhancer is prepared by the following steps:
[0034] Step B1, 1.5 g zinc nitrate hexahydrate and 0.4 g 2,3,5,6-tetrafluoroterephthalic acid were ultrasonically dispersed in 30 mL N,N-dimethylformamide for 30 min, 1 mL distilled water was added and stirred for 10 min, transferred to an autoclave, reacted at 120° C. for 24 h, filtered, washed, soaked in methanol for 72 h, filtered, and dried to obtain Zn-MOF;
[0035] Step B2, sonicate 1 g of Zn-MOF in 100 mL of deionized water for 30 min, then add 0.8 g of magnesium nitrate hexahydrate, 0.6 g of aluminum nitrate nonahydrate and 1.2 g of urea and sonicate for 30 min, then heat to 85 ° C and stir to react for 1.5 h, then transfer to an autoclave, react at 120 ° C for 12 h, filter, wash and dry to obtain Zn-MOF / magnesium aluminum hydrotalcite;
[0036] Step B3, stir 0.2 mL of γ-methacryloxypropyltrimethoxysilane in a mixture of 80 mL of ethanol and 20 mL of deionized water for 30 min, then add 2 g of Zn-MOF / magnesium aluminum hydrotalcite, heat to 35° C. and stir for 3 h, filter, wash and dry to obtain an enhancer.
[0037] Example 2: The modified toughening agent is prepared by the following steps:
[0038] Step A1, 0.075 mol of tetraethyl orthosilicate and 0.045 mol of dimethyldiethoxysilane were mixed and stirred in 20 mL of deionized water for 10 min to form a mixed solution, and then the mixed solution was slowly added dropwise to 80 mL of ethanol, stirred and reacted for 2.5 h, and then 0.02 mol of γ-glycidyloxypropyltrimethoxysilane was slowly added, stirred and reacted for 1 h, and then 2 mL of 10 wt% ammonia water was added, and the mixture was transferred to a 60° C. water bath and allowed to stand for 30 min, centrifuged, washed, and dried to obtain functionalized silicone microspheres;
[0039] Step A2, adding 0.02 mol 2,2-dihydroxymethylpropionic acid, 3.2 g tetrabutylammonium bromide and 100 mL N,N-dimethylformamide to the functionalized organosilicon microspheres, mixing, first purging with nitrogen for 10 min, then reacting under nitrogen and 85° C. for 5 h, rotary evaporation, adding 30 mL ethyl acetate and stirring for 15 min, washing and drying to obtain a hyperbranched organosilicon precursor;
[0040] Step A3, after mixing 12g of hyperbranched organosilicon precursor and 0.85g of potassium hydroxide, nitrogen was purged for 10min, and then the temperature was raised to 100°C under nitrogen conditions, reacted for 3h, cooled to room temperature, 15g of propylene oxide was added, and then the temperature was raised to 70°C for reaction for 4.5h, and then cooled to 25°C, 5.5g of epichlorohydrin was added, stirred and heated to 70°C for reaction for 2.5h, and then 100mL, 25wt% potassium hydroxide solution was added and stirred for 2.5h, washed, and then 7.5g of pentaerythritol phosphate was added at 70°C, stirred for reaction for 3h, washed and dried to obtain a modified toughening agent.
[0041] The enhancer is prepared by the following steps:
[0042] Step B1, 3 g of zinc nitrate hexahydrate and 0.8 g of 2,3,5,6-tetrafluoroterephthalic acid were ultrasonically dispersed in 30 mL of N,N-dimethylformamide for 30 min, 1.5 mL of distilled water was added and stirred for 10 min, transferred to an autoclave, reacted at 120° C. for 24 h, filtered, washed, soaked in methanol for 72 h, filtered, and dried to obtain Zn-MOF;
[0043] Step B2, 1.5 g Zn-MOF was ultrasonicated in 100 mL deionized water for 30 min, and then 1 g magnesium nitrate hexahydrate, 0.75 g aluminum nitrate nonahydrate and 1.55 g urea were added and ultrasonicated for 30 min, and then the temperature was raised to 90 ° C. and stirred for reaction for 2 h, and then transferred to an autoclave, reacted at 120 ° C. for 12 h, filtered, washed and dried to obtain Zn-MOF / magnesium aluminum hydrotalcite;
[0044] Step B3, stir 0.5 mL of γ-methacryloxypropyltrimethoxysilane in a mixture of 80 mL of ethanol and 20 mL of deionized water for 30 min, then add 3 g of Zn-MOF / magnesium aluminum hydrotalcite, heat to 45° C. and stir for 4 h, filter, wash and dry to obtain an enhancer.
[0045] Example 3: The modified toughening agent is prepared by the following steps:
[0046] Step A1, 0.1 mol of tetraethyl orthosilicate and 0.06 mol of dimethyldiethoxysilane were mixed and stirred in 20 mL of deionized water for 10 min to form a mixed solution, and then the mixed solution was slowly added dropwise to 80 mL of ethanol, stirred for reaction for 3 h, and then 0.03 mol of γ-glycidyloxypropyltrimethoxysilane was slowly added, stirred for reaction for 1.5 h, and then 3 mL of 10 wt% ammonia water was added, and the mixture was transferred to a 60° C. water bath and allowed to stand for 30 min, centrifuged, washed, and dried to obtain functionalized organosilicon microspheres;
[0047] Step A2, adding 0.03 mol 2,2-dihydroxymethylpropionic acid, 4.8 g tetrabutylammonium bromide and 100 mL N,N-dimethylformamide to the functionalized organosilicon microspheres, mixing, first purging with nitrogen for 10 min, then reacting under nitrogen and 90° C. for 6 h, rotary evaporation, adding 30 mL ethyl acetate and stirring for 15 min, washing and drying to obtain a hyperbranched organosilicon precursor;
[0048] Step A3, after mixing 16g of hyperbranched organosilicon precursor and 1.2g of potassium hydroxide, nitrogen was purged for 10min, and then the temperature was raised to 110°C under nitrogen conditions, reacted for 4h, cooled to room temperature, 20g of propylene oxide was added, and then the temperature was raised to 80°C for reaction for 6h, and then cooled to 30°C, 8g of epichlorohydrin was added, stirred and heated to 80°C for reaction for 3h, and then 100mL of 25wt% potassium hydroxide solution was added and stirred for 3h, washed, and then 10g of pentaerythritol phosphate was added at 80°C, stirred and reacted for 3.5h, washed and dried to obtain a modified toughening agent.
[0049] The enhancer is prepared by the following steps:
[0050] Step B1, 4.5 g zinc nitrate hexahydrate and 1.2 g 2,3,5,6-tetrafluoroterephthalic acid were ultrasonically dispersed in 30 mL N,N-dimethylformamide for 30 min, 2 mL distilled water was added and stirred for 10 min, transferred to an autoclave, reacted at 120° C. for 24 h, filtered, washed, soaked in methanol for 72 h, filtered, and dried to obtain Zn-MOF;
[0051] Step B2, sonicate 2 g of Zn-MOF in 100 mL of deionized water for 30 min, then add 1.2 g of magnesium nitrate hexahydrate, 0.9 g of aluminum nitrate nonahydrate and 1.9 g of urea and sonicate for 30 min, then heat to 95 ° C and stir to react for 2.5 h, then transfer to an autoclave, react at 120 ° C for 12 h, filter, wash and dry to obtain Zn-MOF / magnesium aluminum hydrotalcite;
[0052] Step B3, stir 0.8 mL of γ-methacryloxypropyltrimethoxysilane in a mixture of 80 mL of ethanol and 20 mL of deionized water for 30 min, then add 4 g of Zn-MOF / magnesium aluminum hydrotalcite, heat to 55° C. and stir for 5 h, filter, wash and dry to obtain an enhancer.
[0053] Example 4: A method for preparing a corrosion-resistant plastic barrel composite material comprises the following steps:
[0054] 70 parts of polypropylene resin, 20 parts of polyethylene resin, 8 parts of the modified toughening agent prepared in Example 1, 10 parts of the reinforcing agent prepared in Example 1, 0.3 parts of antioxidant 1010, 2 parts of calcium stearate, and 1 part of maleic anhydride grafted polypropylene;
[0055] The raw materials were weighed in parts by weight, and polypropylene resin, polyethylene resin, maleic anhydride grafted polypropylene and the modified toughening agent prepared in Example 1 were added into a stirrer and stirred at 130° C. for 2 h. The reinforcing agent prepared in Example 1, antioxidant 1010 and calcium stearate were added and mixed and stirred evenly to obtain a mixture. The mixture was then put into a twin-screw extruder for extrusion and granulation to obtain a corrosion-resistant plastic barrel composite material.
[0056] Example 5: A method for preparing a corrosion-resistant plastic barrel composite material comprises the following steps:
[0057] 75 parts of polypropylene resin, 25 parts of polyethylene resin, 12 parts of the modified toughening agent prepared in Example 2, 15 parts of the reinforcing agent prepared in Example 2, 1680.45 parts of antioxidant, 3 parts of calcium stearate, and 2 parts of maleic anhydride grafted polypropylene;
[0058] The raw materials were weighed by weight, and polypropylene resin, polyethylene resin, maleic anhydride grafted polypropylene and the modified toughening agent prepared in Example 2 were added into a stirrer, and stirred at 140° C. for 3 h. The reinforcing agent prepared in Example 2, antioxidant 168 and calcium stearate were added and mixed and stirred evenly to obtain a mixture. The mixture was then put into a twin-screw extruder for extrusion and granulation to obtain a corrosion-resistant plastic barrel composite material.
[0059] Example 6: A method for preparing a corrosion-resistant plastic barrel composite material comprises the following steps:
[0060] 80 parts of polypropylene resin, 30 parts of polyethylene resin, 15 parts of the modified toughening agent prepared in Example 3, 20 parts of the reinforcing agent prepared in Example 3, 1680.6 parts of antioxidant, 3 parts of maleic anhydride grafted polypropylene, and 4 parts of calcium stearate;
[0061] The raw materials were weighed by weight, and polypropylene resin, polyethylene resin, maleic anhydride grafted polypropylene and the modified toughening agent prepared in Example 3 were added into a stirrer, and stirred at 150° C. for 4 hours. The reinforcing agent prepared in Example 3, antioxidant 168 and calcium stearate were then added and mixed and stirred evenly to obtain a mixture. The mixture was then put into a twin-screw extruder for extrusion and granulation to obtain a corrosion-resistant plastic barrel composite material.
[0062] Comparative Example 1: This comparative example is a plastic barrel composite material, which differs from Example 6 in that the modified toughening agent prepared in Example 3 is replaced by commercially available thermoplastic elastomer POE, and the rest are the same.
[0063] Comparative Example 2: This comparative example is a plastic barrel composite material. The difference from Example 6 is that the reinforcing agent prepared in Example 3 is replaced by magnesium aluminum hydrotalcite treated with a coupling agent (the specific steps are the same as step B3 of Example 3), and the rest are the same.
[0064] Comparative Example 3: This comparative example is a plastic barrel composite material. The difference from Example 6 is that the reinforcing agent prepared in Example 3 is replaced by Zn-MOF treated with a coupling agent (the specific steps are the same as step B3 of Example 3), and the rest are the same.
[0065] The performance tests of the plastic barrel composite materials prepared in Examples 4-6 and Comparative Examples 1-3 were performed:
[0066] Tensile strength test: According to the method specified in GB / T1040-2018, the tensile strength test was carried out at a tensile rate of 10 mm / min;
[0067] Notched impact strength test: ISO180-2000 is used to test the material's cantilever beam notched impact strength, A-type notch, and the impact pendulum capacity is 5.5J;
[0068] Weathering test: After drying the sample in a blast oven at 120°C for 4 hours, the sample was injection molded into a smooth color plate with a size of 83mm×54mm×2m and no leather grain on the surface by an injection molding machine. The injection molding condition was 240°C and the injection molding cycle was 5s. According to the provisions of GB / T 16422.3-2014 Cycle 1, the test was carried out in a UVA-340 test chamber: 8 hours of drying + 4 hours of condensation is 1 cycle, and 6 cycles are carried out for a total of 72 hours. Before and after the color plate is placed in the test chamber, the color plate data under the D65 light source are measured with an X-rite7000A colorimeter, and the color difference before and after is compared, which is represented by △E. The larger the △E, the greater the color difference.
[0069] Corrosion resistance test: The corrosion resistance of the samples was tested according to GB / T 10125-2021. 前 -m 后 ) / m 前]×100%;
[0070] The test results are shown in Table 1:
[0071] Table 1: Performance test results
[0072]
[0073] As can be seen from Table 1, the tensile strength, notched impact strength, weather resistance and corrosion resistance of the plastic barrel composite material prepared by the present invention are tested. The tensile strength is in the range of (33.3-35.5) MPa, and the notched impact strength is in the range of (66.8-68.1) KJ / m 2 The weather resistance is within the color difference range of 0.4-0.5, and the mass reduction rate is within (0.023-0.026)%, indicating that the composite material has excellent toughness, weather resistance and corrosion resistance.
[0074] The above contents are merely examples and explanations of the concept of the present invention. The technicians in this technical field may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the scope defined by the concept of the invention, they should all fall within the protection scope of the present invention.
Claims
1. A corrosion-resistant plastic barrel composite material, characterized in that: The invention comprises the following raw materials in parts by weight: 70-80 parts of polypropylene resin, 20-30 parts of polyethylene resin, 8-15 parts of modified toughening agent, 10-20 parts of reinforcing agent, 0.3-0.6 parts of antioxidant, 2-4 parts of lubricant, and 1-3 parts of maleic anhydride grafted polypropylene; The modified toughening agent is prepared by the following steps: Step A1, tetraethyl orthosilicate and dimethyldiethoxysilane are mixed and stirred in deionized water for 10 minutes to form a mixed solution, and then the mixed solution is slowly added dropwise to ethanol, stirred and reacted for 2-3 hours, and then γ-glycidyloxypropyltrimethoxysilane is slowly added, stirred and reacted for 0.5-1.5 hours, and then 10wt% ammonia water is added, and the mixture is transferred to a 60°C water bath and allowed to stand for 30 minutes, centrifuged, washed, and dried to obtain functionalized silicone microspheres; Step A2, adding 2,2-dihydroxymethylpropionic acid, tetrabutylammonium bromide and N,N-dimethylformamide to the functionalized organosilicon microspheres, mixing, first purging with nitrogen for 10 minutes, then reacting under nitrogen at 80-90° C. for 4-6 hours, rotary evaporation, adding ethyl acetate and stirring for 15 minutes, washing and drying to obtain a hyperbranched organosilicon precursor; Step A3, after mixing the hyperbranched organosilicon precursor and potassium hydroxide, nitrogen is purged for 10 minutes, and then the temperature is raised to 90-110°C under nitrogen conditions, and the reaction is carried out for 2-4 hours, and then the temperature is reduced to room temperature and propylene oxide is added, and then the temperature is raised to 60-80°C and the reaction is carried out for 3-6 hours, and then the temperature is reduced to 20-30°C, epichlorohydrin is added, and the temperature is raised to 60-80°C with stirring and the reaction is carried out for 2-3 hours, and then 25wt% potassium hydroxide solution is added and stirred for 2-3 hours, and then pentaerythritol phosphate is added at 60-80°C, and the reaction is stirred for 2.5-3.5 hours, washed, and dried to obtain a modified toughening agent.
2. The corrosion-resistant plastic barrel composite material according to claim 1, characterized in that: In step A1, the usage ratio of tetraethyl orthosilicate, dimethyldiethoxysilane, deionized water, ethanol, γ-glycidyloxypropyltrimethoxysilane and ammonia water is 0.05-0.1 mol: 0.03-0.06 mol: 20 mL: 80 mL: 0.01-0.03 mol: 1-3 mL.
3. The corrosion-resistant plastic barrel composite material according to claim 1, characterized in that: In step A2, the usage ratio of 2,2-dihydroxymethylpropionic acid, tetrabutylammonium bromide, N,N-dimethylformamide and ethyl acetate is 0.01-0.03 mol: 1.6-4.8 g: 100 mL: 30 mL.
4. The corrosion-resistant plastic barrel composite material according to claim 1, characterized in that: In step A3, the usage ratio of the hyperbranched organosilicon precursor, potassium hydroxide, propylene oxide, epichlorohydrin, potassium hydroxide solution and pentaerythritol phosphate is 8-16 g: 0.5-1.2 g: 10-20 g: 3-8 g: 100 mL: 5-10 g.
5. The corrosion-resistant plastic barrel composite material according to claim 1, characterized in that: The antioxidant is one of antioxidant 1010 and antioxidant 168, and the lubricant is calcium stearate.
6. The corrosion-resistant plastic barrel composite material according to claim 1, characterized in that: The enhancer is prepared by the following steps: Step B1, ultrasonically disperse zinc nitrate hexahydrate and 2,3,5,6-tetrafluoroterephthalic acid in N,N-dimethylformamide for 30 minutes, add distilled water and stir for 10 minutes, transfer to an autoclave, react at 120°C for 24 hours, filter, wash, soak in methanol for 72 hours, filter, and dry to obtain Zn-MOF; Step B2, sonicating Zn-MOF in deionized water for 30 minutes, then adding magnesium nitrate hexahydrate, aluminum nitrate nonahydrate and urea and sonicating for 30 minutes, then heating to 85-95°C and stirring to react for 1.5-2.5 hours, then transferring to an autoclave, reacting at 120°C for 12 hours, filtering, washing and drying to obtain Zn-MOF / magnesium aluminum hydrotalcite; Step B3, stirring γ-methacryloxypropyltrimethoxysilane in a mixture of ethanol and deionized water for 30 minutes, then adding Zn-MOF / magnesium aluminum hydrotalcite, heating to 35-55° C. and stirring for reaction for 3-5 hours, filtering, washing and drying to obtain an enhancer.
7. The corrosion-resistant plastic barrel composite material according to claim 6, characterized in that: In step B1, the usage ratio of zinc nitrate hexahydrate, 2,3,5,6-tetrafluoroterephthalic acid, N,N-dimethylformamide and distilled water is 1.5-4.5 g: 0.4-1.2 g: 30 mL: 1-2 mL.
8. The corrosion-resistant plastic barrel composite material according to claim 6, characterized in that In step B2, the dosage ratio of Zn-MOF, deionized water, magnesium nitrate hexahydrate, aluminum nitrate nonahydrate and urea is 1-2 g: 100 mL: 0.8-1.2 g: 0.6-0.9 g: 1.2-1.9 g.
9. The corrosion-resistant plastic barrel composite material according to claim 6, characterized in that: In step B3, the usage ratio of γ-methacryloxypropyltrimethoxysilane, ethanol, deionized water and Zn-MOF / magnesium aluminum hydrotalcite is 0.2-0.8 mL: 80 mL: 20 mL: 2-4 g.
10. A method for preparing the corrosion-resistant plastic barrel composite material according to any one of claims 1 to 9, characterized in that: The following steps are involved: Weigh the raw materials by weight, add polypropylene resin, polyethylene resin, maleic anhydride grafted polypropylene and modified toughening agent into a stirrer, stir at 130-150°C for 2-4 hours, then add a reinforcing agent, an antioxidant and a lubricant, mix and stir evenly to obtain a mixture, then put the mixture into a twin-screw extruder for extrusion and granulation to obtain a corrosion-resistant plastic barrel composite material.
Citation Information
Patent Citations
Toughened PP plastic bucket and preparation method thereof
CN108276679A
High-strength plastic bucket composite material and preparation method thereof
CN117844095A